Combining analytical chemistry and traceology: An innovative approach applied to Mesoamerican mirrors found at the Sojo site (Costa Rica) - Ménager, Matthieu (2021)
An innovative approach based on the combination of spectroscopy and traceology was used in order to analyse iron ore mirrors excavated at the Sojo site (Chibcha area, present-day Costa Rica) in the northern Pacific region of Costa Rica (AD 300 to AD 500–600). Such mirrors were prestigious artefacts related to power, shamanism and divination during the Classic Period in the Maya area. Stone bases, adhesives and tesserae were characterised using FT-IR, SEM/EDX and Raman Spectroscopy, as well as X-Ray Fluorescence (XRF) and the techniques used in their manufacture were elucidated using traceology. Similar materials were found to have been used for all the bases, tesserae, adhesives and coatings of the different mirrors. Furthermore, two tessera-shaped fragments were most probably part of a composite mirror, manufactured by sticking hematite nodules onto stone tesserae using a clay mixed with an organic binder. Chert and obsidian tools were used to make, respectively, perforations and edges on all mirror bases, and the two main types of abrasion of the base surfaces were found to have been made with basalt or limestone. These analyses indicate a probable Maya origin as their manufacturing traces distin- guish them from Teotihuacan mirrors.